Lugar e identidade: o legado sertanejo do povo nortense do Tocantins - Elzimar Pereira Nascimento Ferraz; Elias da Silva (Desafios, 2016)
The historical development of the northern end of Tocantins is intrinsically linked to a double bond: the place and identity. In this perspective, the text approaches aspects of the settlement process in the Parrot's Beak, considering, among other characteristics, ownership of free land for the constituent work place in order that links the land from production to residence, the coexistence and socio-cultural practices resulting ultimately in the identity construction that feeds on humanitarian values. The methodological procedure adopted included a literature review subsidized especially by authors of different theoretical affiliations, but convergent to the subject. In this study, we seek to establish the relationship between place and identity in designing training subjects as broader social process in which it is effective for the exchange of knowledge, attitudes and ways of life not institutionalized by school standards, which help to understand the basis of uses and customs of nortense population arising from traditional rural life.